Fragmentation dynamics in the Sierra Madre Oriental and its impact on the distribution of birds - Castro-Navarro, Jaime; Sahagún Sánchez, Francisco Javier; Reyes-Hernández, Humberto (Instituto de Ecología, A.C., 2017)
Fragmentation and land use cover change are key factors for global biodiversity loss. In this work, we analyzed the processes of fragmentation in land use cover in the region of the Sierra Madre Oriental in San Luis Potosi, Mexico, to assess the impact on the distribution of birds and important areas for conservation. Fieldwork was conducted and distribution records of birds were collected, from which species distribution models with MaxEnt were developed. This information was compared with fragmentation data obtained from landscape metrics. The results indicate that natural land cover is prone to fragmentation, while land use (i.e. agriculture) tends to connect and increase in area. Both, Central and Southwestern regions have the greatest tendency to land cover fragmentation, leading to a high heterogeneity in the landscape. This affects the distribution areas of 34% of modeled species due to loss of connectivity between habitats and rising edges. These results confirm the importance of the region as a center of high bird diversity and highlights the need for short-term conservation actions to maintain the distribution areas of importance for birds.